Keeping or changing? Two different cultural adaptation strategies in the domestic use of home country food plant and herbal ingredients among Albanian and Moroccan migrants in Northwestern Italy - Michele Fontefrancesco; Charles Barstow; Francesca Grazioli; Hillary Lyons; Giulia Mattalia; Mattia Marino; Anne E. McKay; Renata Sõukand; Paolo Corvo; Andrea Pieroni (BMC, 2019)
Abstract Background Ethnobotanical field studies concerning migrant groups are crucial for understanding temporal changes of folk plant knowledge as well as for analyzing adaptation processes. Italy still lacks in-depth studies on migrant food habits that also evaluate the ingredients which newcomers use in their domestic culinary and herbal practices. Methods Semi-structured and open in-depth interviews were conducted with 104 first- and second-generation migrants belonging to the Albanian and Moroccan communities living in Turin and Bra, NW Italy. The sample included both ethnic groups and genders equally. Results While the number of plant ingredients was similar in the two communities (44 plant items among Albanians vs 47 plant items among Moroccans), data diverged remarkably on three trajectories: (a) frequency of quotation (a large majority of the ingredients were frequently or moderately mentioned by Moroccan migrants whereas Albanians rarely mentioned them as still in use in Italy); (b) ways through which the home country plant ingredients were acquired (while most of the ingredients were purchased by Moroccans in local markets and shops, ingredients used by Albanians were for the most part informally "imported" during family visits from Albania); (c) quantitative and qualitative differences in the plant reports mentioned by the two communities, with plant reports recorded in the domestic arena of Moroccans nearly doubling the reports recorded among Albanians and most of the plant ingredients mentioned by Moroccans representing "medicinal foods". Conclusion A large portion of the differences shown by the two communities are linked to different methods of procurement of home country gastronomic botanical ingredients, the different transnational informal exchanges that exist between Italy and migrants' home countries, the presence of markets and ethnic shops in Italy selling these items, and the different degree of difficulty in accessing public health services. The observed divergences were also clearly related to very diverse adaptation strategies, i.e., processes of negotiating and elaborating Albanian and Moroccan cultural identities.